Indirect and Neuropsychological Indicators of Pedophilia. (August 2021) - Rosburg, Timm; Pflueger, Marlon O.; Mokros, Andreas; Boillat, Coralie; Deuring, Gunnar; Spielmann, Thorsten; Graf, Marc
The present study aimed to differentiate pedophilic child sex offenders (CSOs) from nonoffending controls (CTLs), as well as contact from noncontact CSOs. For this purpose, we investigated 21 contact CSOs, 20 noncontact CSOs (child pornography offenders), as well as 21 CTLs on neuropsychological test measures and indirect test measures of sexual interest. Multiple logistic regression models showed that three parameters of indirect tests and two neuropsychological test parameters allowed the differentiation of CSOs from CTLs with a maximum accuracy of 87%. The profile of contact and noncontact CSOs was remarkably similar and the optimal model for this group differentiation had a maximum accuracy of 66%, with slightly increased levels of risk-taking behavior and greater susceptibility for perceptual interference in contact CSOs than in noncontact CSOs. The findings suggest that standardized, objective methods can support the assessment of sexual offenders against children in forensic psychiatry and legal psychology.